Hydration Structures and Dynamics of In3+ Ion based on Classical Molecular Dynamics Simulation - Novan A. A. Permana; Suwardi Suwardi (Indonesian Journal of Chemistry and Environment, 2021)
The hydration structures and dynamics of In3+ ion have been studied using classical Molecular Dinamics (MD) simulation. The best basis sets were optimized to construct the 2-bodies, 3-bodies correction equations, and analysis of the trajectory file of the simulation results in the form of the parameter of a solvation structure such as RDF, CND, ADF, and dynamic properties, namely the migration of water ligands between the hydration shells. The results showed that the hydration structure of the In3+ ion is In(H2O)93+ and In(H2O)63+, respectively. The geometric arrangement of In3+ hydration obtained through the simulation of classical Molecular Dynamics 2-bd MM 2-bd corrected 3-bd effect is octahedral, which agrees with experimental data and shows the importance of 3-bd correction. The exchange of H2O ligands between the first and second shell or vice versa was not observed during the classical Molecular Dynamics simulation process (2-body + 3-body potential). The hydration structure of In3+ in the first shell was relatively stable.